Images in Medical Practice Vol.28(3) - Siddiqui, MMR; Islam, QT; Hossain, A; Mahbub, MS (Journal of Bangladesh College of Physicians and Surgeons, 2010)
DOI: 10.3329/jbcps.v28i3.6518 J Bangladesh Coll Phys Surg 2010; 28: 202